Give me the answers to thissss plssss rnnnn asapppp!!!!
![Give me the answers to thissss plssss rnnnn asapppp class=](https://us-static.z-dn.net/files/d37/5a835312baa0d7ce79117ad796695c4b.png)
[tex]\\ 1. (3x ^{2} + 2xy + 7) - (6x ^{2} - 4xy + 3) \\ = 3x ^{2} + 2xy + 7 - 6x ^{2} + 4xy - 3 \\ = 3x ^{2} - {6x}^{2} + 2xy + 4xy + 7 - 3 \\ = { - 3x}^{2} + 6xy + 4 \\ 2. \: {9x}^{2} - 2x + 3 - ( {4x}^{2} + 7x - 5) \\ = 9x ^{2} - 2x + 3 - 4x ^{2} - 7x + 5 \\ = {9x}^{2} - {4x}^{2} - 2x - 7x + 3 + 5 \\ = {5x}^{2} - 9x + 8 \\ 3. \: {x}^{2} - 5x + 6 \\ = {x}^{2} - (3 + 2)x + 6 \\ = {x}^{2} - 3x - 2x + 6 \\ = x(x - 3) - 2(x - 3) \\ = (x - 3)(x - 2) \\ hope \: it \: helps \\ good \: luck \: on \: your \: assignment[/tex]
Answer with step by step explanation
[tex](1)(3 {x}^{2} + 2xy + 7) - (6 {x}^{2} - 4xy + 3) \\ 3 {x}^{2} + 2xy + 7 - 6 {x}^{2} + 4xy - 3 \\ = - 3 {x}^{2} + 6xy + 4[/tex]
[tex](2)9 {x}^{2} - 2x + 3 - (4 {x}^{2} + 7x - 5) \\ 9 {x}^{2} - 2x + 3 - 4 {x}^{2} - 7x + 5 \\ = 5 {x}^{2} - 9x + 8[/tex]
[tex](3) {x}^{2} - 5x + 6 \\ {x}^{2} - 3x - 2x + 6 \\ x(x - 3) - 2(x - 3) \\ (x - 2)(x - 3)[/tex]
hope this helps
brainliest appreciated
good luck! have a nice day!